Trees, grasses and crops people and plants in sub-Saharan Africa and beyond - Eichhorn, Barbara 1967-; Höhn, Alexa 1968- (Verlag Dr. Rudolf Habelt GmbH, 2019)
In 2019, Prof. Dr. Katharina Neumann had been head of the workgroup on African Archaeobotany at the Institute for Archaeological Sciences, Goethe University in Frankfurt am Main for 25 years. In honor of this anniversary and to commemorate the achievements made and inspired by Katharina in the field of African Archaeobotany, the editors - two long-time colleagues - have compiled this Festschrift. The title "Trees, Grasses and Crops - People and Plants in Sub-Saharan Africa and Beyond" refers to both the plant groups Katharina has been particularly interested in throughout her academic career and the centerpiece of her research, the correlation between people and plants. Human actions such as food procurement, plant cultivation and domestication affect single plant species as well as plant communities. Together with the environment, they constitute a dynamic network of conditions and consequences. Different ways of life and different modes of subsistence have influenced past environments throughout Africa and beyond to varying degrees. This volume demonstrates the multiplicity of these aspects in more than 25 contributions: possibilities of wild plant food procurement in various regions of the continent and beyond, pre-domestication cultivation and agricultural transitions, questions of different modes of plant cultivation, paleoenvironmental reconstructions, exploitation and changes of past and present environments, whether by anthropogenic and/or climatic drivers. The papers comprise the academic fields of archaeobotany, archaeology, botany, and geography and represent a wide range of methods applied in the fields, such as analyses of phytoliths, pollen, seeds and wood charcoal as well as geomorphological forms, soil profiles, rock engravings, and many more ..
Festschrift für Katharina Neumann zum Anlass ihres 25-jährigen Jubiläums als Leiterin der Arbeitsgruppe für Afrikanische Archäobotanik in der Abteilung Vor- und Frühgeschichte des Instituts für Archäologische Wissenschaften an der Goethe-Universität
Literaturverzeichnis Katharina Neumann: Seite 11-16. - Literaturangaben
Keywords: Neumann, Katharina; Archäobotanik; Festschrift; Aufsatzsammlung